"Athletic Identity Measurement Scale": Translation, Adaptation and Validation for Brazil - Walan Robert da Silva; Elisa Pinheiro Ferrari; Thiago Emannuel Medeiros; Kamyla Thais Dias de Freitas; Claudio Marcelo Tkac; Fernando Luiz Cardoso (Universidade Estadual Paulista (UNESP), 2016)
Abstract The aim of this study was to translate, adapt and validate the version of the Athletic Identity Measurement Scale (AIMS) for Brazilian Portuguese. The methodological procedures were conducted according to international recommendations: translation, back-translation, review by a board of experts, empirical fieldwork testing and inferential statistical analyses. The psychometric properties were evaluated by applying the translated scale to 127 university students. Reproducibility was assessed through stability and homogeneity assessment. Validity was assessed by comparing the scores obtained from the athletes and university students. The results showed good internal consistency (α = 0.78), when item 3 was removed and the Cronbach's alpha value increased to 0.82. Through factor analysis, we verified that the items had loadings in two domains. Intra-class correlation coefficient for test and retest was 0.91. Comparison between athletes and university students showed good discriminant validity. According the cultural adaptation process the adapted instrument has excellent psychometric properties and is reliable for the Brazilian culture.